100 photographs : the most influential images of all time - Goldberger, Ben; Dyer, Geoff; Von Drehle, David, 1961- (Time Books, an imprint of Time Inc. Books, 2015)
"An exploration of the 100 photographs that shaped the human experience." -- Page [4] cover.